2018
DOI: 10.1155/2018/1232785
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein as a Predictive Marker for Patients with Hepatitis B-Related Acute-on-Chronic Liver Failure

Abstract: Background and Aims The value of alpha-fetoprotein (AFP) in hepatitis B-related acute-on-chronic liver failure (HBACLF) is not fully understood. The present study aimed to evaluate the prognostic effect of AFP on the prediction of HBACLF outcomes. Methods We investigated a cohort of patients with HBACLF admitted from January 2013 to May 2017. The endpoint of followup was 180 days, death, or liver transplantation. AFP concentrations were estimated on admission. To make statistical comparisons, we used chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…A histologic study disclosed that AFP synthesis is augmented in the early regenerative phase after liver injury; in particular, proliferation of AFP (+) acinary‐arranged hepatocytes appears to be a more efficient pathway for hepatic regeneration 23 . Furthermore, some clinical studies have suggested that serum AFP level could be a good prognostic marker for better outcomes not only in patients with acute hepatic failure but also in those with acute‐on‐chronic liver failure 24,25 . Thus, elevated AFP levels in the absence of HCC may indicate active hepatocyte regeneration and presage early re‐compensation.…”
Section: Discussionmentioning
confidence: 99%
“…A histologic study disclosed that AFP synthesis is augmented in the early regenerative phase after liver injury; in particular, proliferation of AFP (+) acinary‐arranged hepatocytes appears to be a more efficient pathway for hepatic regeneration 23 . Furthermore, some clinical studies have suggested that serum AFP level could be a good prognostic marker for better outcomes not only in patients with acute hepatic failure but also in those with acute‐on‐chronic liver failure 24,25 . Thus, elevated AFP levels in the absence of HCC may indicate active hepatocyte regeneration and presage early re‐compensation.…”
Section: Discussionmentioning
confidence: 99%
“…9). These results may really meet the fact that alteration in the redox status would stimulate the entire inflammatory cascade including the activation of a series of transcription factors [79,80,81] . AFP is regarded as a biomarker of proliferating liver stem cells under conditions of liver injury [82].…”
Section: Discussionmentioning
confidence: 88%
“…It can clearly be seen the expression of TNF-αandIL6 is about 70%. These findings may ensure that the entire inflammatory cascade, including the activation of transcription factors, is activated when the redox status is attached [ 46 , 47 , 48 ]. However, these parameters were remodulated and downregulated by mustard extract treatment in both normal and its nano form either pre-or post TAA intoxication.…”
Section: Discussionmentioning
confidence: 99%